Acupuncture combined with auricular acupressure for smoking cessation and its effects on tobacco dependence and smoking behavior among Hong Kong smokers: a multicenter pilot clinical study - Lai Fun Ho; Wai Kwan Ho; Ling Ling Wong; Sze Wan Chiu; Shuk Yu Tang; Chun Ming Wong; Kin San Chan; Chi Lan Lam; Min Chen; Kam Leung Chan; Guohua Lin; Bacon Fung-Leung Ng; et al. (BMC, 2022)
Abstract Background Acupuncture combined with auricular acupressure has been used as a complementary and alternative treatment for smoking cessation in Hong Kong for over 10 years. This study aimed to investigate the success rates of smoking cessation posttreatment, and to evaluate treatment effects on tobacco dependence, smoking behavior, anxiety levels, and sleep disturbances between successful and unsuccessful quit smokers in Hong Kong. Methods This prospective, multicenter clinical study conducted between September 2020 and February 2022 in Hong Kong was part of the Guangdong-Hong Kong-Macau Greater Bay Area project on smoking cessation. Thirty eligible current smokers (mean age 47.10 years; 40% female) were recruited and received a combination of standardized acupuncture and auricular acupressure treatments twice weekly for 8 weeks. The primary outcome was the success rate of smoking cessation at week 24. The secondary outcomes were the success rates of smoking cessation at weeks 8 and 16, exhaled carbon monoxide (CO) levels, and changes in scores on the Fagerström Test for Nicotine Dependence (FTND), Autonomy Over Smoking Scale (AUTOS), Hamilton Anxiety Rating Scale (HAM-A), Self-rating Anxiety Scale (SAS), and Pittsburgh Sleep Quality Index (PSQI). Adverse events were also recorded. Results Of 30 eligible participants, 28 completed 6 or more treatment sessions; all completed follow-up assessments. At week 24, the success rate of smoking cessation was 46.67%. The successfully quit rates at weeks 8 and 16 were 36.67% and 43.33%, respectively. The overall change in mean FTND scores from baseline improved significantly from weeks 2 to 24 (P < 0.05), with the successful quit group showing significantly greater improvement between weeks 8 and 24 (P < 0.01). Compared with baseline values, there were significant reductions in mean AUTOS scores from weeks 6 to 24 (P < 0.001), with the successful quit group showing greater improvement at weeks 16 (P = 0.04) and 24 (P < 0.001). No significant changes were detected in exhaled CO levels or HAM-A, SAS, and PSQI scores. No study-related adverse events were observed. Conclusions Acupuncture combined with auricular acupressure could be an effective alternative treatment for smoking cessation and reduction of tobacco dependence among Hong Kong smokers. Trial registration Chinese Clinical Trial Registry, No. ChiCTR2000033650. Registered on June 7, 2020. http://www.chictr.org.cn/showproj.aspx?proj=54866